Establishment of Nothofagus pumilio at upper treelines across a precipitation gradient in the northern Patagonian Andes - Srur, Ana Marina; Villalba, Ricardo; Rodriguez Catón, Milagros Rocío; Amoroso, Mariano Martin; Marcotti, Eugenia (Arctic, Antarctic, and Alpine Research)
Trees at upper treelines are exposed to more extreme environmental conditions than those at lower elevations. Climate changes at the upper treeline facilitate the establishment or intensify the mortality of trees and, consequently, affect species distributions. The structure and density of individuals of Nothofagus pumilio above the upper treeline, together with their temporal patterns of establishment, were determined in three sites located along a west-east precipitation gradient across the Patagonian Andes. Patterns of tree establishment were compared to regional variations in temperature and precipitation, as well as to indexes of atmospheric circulation that modulate northern Patagonian climate. Mesic and dry sites along the moisture gradient have a lower density of newly established trees; however, individuals show larger basal diameters and greater annual growth rates, heights, and number of branches than those established in humid sites. In wet areas, the high density of individuals reflects the higher rates of N. pumilio establishment and survival. At drier treelines, low snow persistence, associated with longer growing seasons, appears to be related to the larger size of individuals. At all sites, patterns of tree establishment are characterized by an abrupt increase in recruitment starting in the mid-1970s and a marked decrease in the late 1990s. The onset of tree establishment above the treeline coincides with an increase in regional spring-summer temperature in the year 1977, concurrent with the negative-to-positive shift in the phase of the Pacific Decadal Oscillation (PDO). In contrast, the decrease in N. pumilio establishment since the late 1990s coincides with an opposite shift (positive to negative) in the PDO. This recent change in the PDO phase did not significantly modify the mean values but increased the interannual variability of the spring-summer temperatures in the region. Changes in the PDO, which encompasses complex variations in environmental conditions at the upper treeline, are more ...